Lifestyle risk factors for cardiovascular disease and diabetic risk in a sedentary occupational group: the Galway taxi driver study. (May 2016) - Martin, W.; Sharif, F.; Flaherty, G.
Abstract Background Taxi drivers are at increased risk of cardiovascular disease (CVD), something which persists after correcting for the overrepresentation of traditional risk factors for CVD in this cohort. The contribution of lifestyle risk factors to this residually elevated CVD risk remains under-evaluated. Aims We aimed to determine the prevalence of lifestyle risk factors for CVD, self-reported medical risk factors for CVD, and future risk of type 2 diabetes amongst Irish taxi drivers. Methods Male taxi drivers with no history of CVD and type 2 diabetes and working in Galway city in the west of Ireland were invited to participate. Physical activity levels, dietary patterns, anthropometry, smoking, hypertension, hypercholesterolaemia, and Finnish Diabetes Risk Score (FINDRISC) values were recorded in a cross-sectional manner. Results 41 taxi drivers (mean age 56.7 ± 9.8 years) participated. 37 % were insufficiently active based on self-report, although only 8 % objectively achieved 10, 000 steps per day. Mean modified Mediterranean diet score (mMDS) was 4.6 ± 2.2, and only 13 % of participants had a normal body mass index (BMI) or waist circumference (WC). Those who worked for taxi companies tended to have a higher BMI (p  = .07) and WC (p  = .04) by multivariable regression. 22 % were current smokers, although a quit rate of 72 % was observed amongst the 78 % of taxi drivers who had ever smoked. 25 % were at high or very high risk of future type 2 diabetes. Conclusion Lifestyle risk factors for CVD and dysglycaemia are prevalent amongst Irish taxi drivers.